2018
DOI: 10.1002/jaba.450
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive validity and efficiency of ongoing visual‐inspection criteria for interpreting functional analyses

Abstract: Prior research has evaluated the reliability and validity of structured criteria for visually inspecting functional-analysis (FA) results on a post-hoc basis, after completion of the FA (i.e., post-hoc visual inspection [PHVI]; e.g., Hagopian et al., 1997). However, most behavior analysts inspect FAs using ongoing visual inspection (OVI) as the FA is implemented, and the validity of applying structured criteria during OVI remains unknown. In this investigation, we evaluated the predictive validity and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(100 citation statements)
references
References 36 publications
4
93
3
Order By: Relevance
“…Functional analysis graphs for inclusion in the present study were identified from the supplemental material file accompanying the study conducted by Saini et al (). In that study, FA datasets had been identified following a thorough review of studies included in the articles by Hanley et al () and Beavers et al () as well as by additional searches using keywords in PsychINFO, ERIC, JABA , and Google Scholar.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Functional analysis graphs for inclusion in the present study were identified from the supplemental material file accompanying the study conducted by Saini et al (). In that study, FA datasets had been identified following a thorough review of studies included in the articles by Hanley et al () and Beavers et al () as well as by additional searches using keywords in PsychINFO, ERIC, JABA , and Google Scholar.…”
Section: Methodsmentioning
confidence: 99%
“…To provide preliminary evidence for the validity of ANSA, we examined the extent to which the ANSA outcomes were concordant with PHAI, the anchor of comparison, as well as PHVI. The outcome for PHAI was determined by corroborating evidence for each dataset from the original published paper and supplementary material (Saini et al, ). An agreement between ANSA and PHAI was scored if ANSA ascribed the same outcome as the published outcome.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the utility of skilled visual assessment in determining functions of behavior from functional‐analysis outcomes and the development of structured, formal visual‐analysis protocols for functional analyses (e.g., Hagopian et al, ; Roane, Fisher, Kelley, Mevers, & Bouxsein, ; Saini, Fisher, & Retzlaff, ), assessment of differences in levels of problem behavior between conditions is not always straightforward. Figure , for example, shows aggressions per minute from a hypothetical multielement functional analysis.…”
Section: Applications To Behavior‐analytic Datamentioning
confidence: 99%